α-Lactalbumin mRNA-LNP Evokes an Anti-Tumor Effect Combined with Surgery in Triple-Negative Breast Cancer - Yun-Ru He; Heng Xia; Peng Yun; Yuandong Xu; Winson M. J. Ma; Ze-Xiu Xiao; Gao-Feng Zha (MDPI AG, 2024)
Triple-negative breast cancer (TNBC) has been considered a huge clinical unmet need due to its aggressive progression and highly frequent metastasis. mRNA therapeutics supply a potential and versatile immunotherapy of oncology treatment. Here, we developed α-lactalbumin mRNA-lipid nanoparticles (α-LNP) as a potential therapeutical strategy for TNBC. The α-LNP induced the specific IgG antibodies and activated IFN γ-secreting-T cells in vivo. Additionally, the safety of α-LNP also had been demonstrated in vivo. When vaccinated prior to tumor implantation, α-LNP showed a preventive effect against 4T1 tumor growth and extended the survival of the tumor model by activating the memory immune responses. Furthermore, α-LNP administration in combination with surgical removal of neoplasm effectively inhibited the progression and metastasis in the TNBC model. Taken together, our results indicate that the α-LNP vaccine is a promising novel treatment for both therapeutics and prophylactics in TNBC.